2023
DOI: 10.3389/fmicb.2023.1164632
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microbial community in the urban environment: The concordance between conventional culture and nanopore 16S rRNA sequencing

Abstract: IntroductionMicrobes in the built environment have been implicated as a source of infectious diseases. Bacterial culture is the standard method for assessing the risk of exposure to pathogens in urban environments, but this method only accounts for <1% of the diversity of bacteria. Recently, full-length 16S rRNA gene analysis using nanopore sequencing has been applied for microbial evaluations, resulting in a rise in the development of long-read taxonomic tools for species-level classification. Regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…It allows a maximum of 24 unique samples in a single run using the proprietary barcoded-16S primers, limiting the utility in studies aiming for scale in MINION devices. Given that 16S barcoding has been the default and benchmarked choice, many prior published reports of microbiome research using nanopore sequencing are often observed to be limited by scale in individual runs (15, 18, 4244). In order to increase the scale of the captured microbiome, we sought to adopt the Native Barcoding Kit – 96 (SQK-NBD114.96) instead to natively barcode the sample specific amplicons (total 96 samples) entailing end-repair/end-prep, PCR free barcoding and adapter ligation.…”
Section: Methodsmentioning
confidence: 99%
“…It allows a maximum of 24 unique samples in a single run using the proprietary barcoded-16S primers, limiting the utility in studies aiming for scale in MINION devices. Given that 16S barcoding has been the default and benchmarked choice, many prior published reports of microbiome research using nanopore sequencing are often observed to be limited by scale in individual runs (15, 18, 4244). In order to increase the scale of the captured microbiome, we sought to adopt the Native Barcoding Kit – 96 (SQK-NBD114.96) instead to natively barcode the sample specific amplicons (total 96 samples) entailing end-repair/end-prep, PCR free barcoding and adapter ligation.…”
Section: Methodsmentioning
confidence: 99%
“…The prompt development of HTS led to the sequencing of full-length 16S rRNA by nanopore technology that implemented the taxonomy based on culture-based methods, particularly for the pathogenic species ( Lee et al, 2023 ).…”
Section: Omic Approaches To Detect and Characterize The Be B...mentioning
confidence: 99%
“…Regardless these meta-analysis studies and mock community assessments are valuable in defining the accuracy, sensitivity, and specificity of microbial classifiers, a complex BE microbial community could provide a more realistic understanding of biological classifiers and mechanistic relationships ( Lee et al, 2023 ). However, surveys regarding a genomic-functional reconstruction often lack information about gene transcription, translation, and protein affinity and activity could be limiting ( Hester et al, 2019 ).…”
Section: Omic Approaches To Detect and Characterize The Be B...mentioning
confidence: 99%
“…The pathogens are not only found in the host but also the environment. Therefore, the detection of pathogens in different environments such as soil, river, water, and air samples was conducted using ONT [45,[52][53][54][55]. The nanopore sequencing method was also successfully applied for the detection of antibiotic resistance genes in microbes [45,53].…”
Section: Nanopore Sequencing Technology In Pathogenic Diagnosticsmentioning
confidence: 99%